Unexpected transformation of n.c.a. [111In]InCl3 in stock solutions into an unreactive [111In]In-species. (February 2022) - Giammei, Carolina; Jouini, Nedra; Brandt, Marie R.; Frey, Stefanie; Mindt, Thomas L.; Cardinale, Jens
Abstract: While performing multiple indium-111 labeling of DOTA-modified peptides from a single batch of [ 111 In]InCl3, inconsistent radiochemical yields were observed. We found that the formation of a radioactive impurity in the [ 111 In]InCl3 stock solution hampered the reactivity of the indium-111 during radiolabeling reactions. The formation of this unknown 111 In-species could be successfully suppressed by increasing the concentration of chloride ions in the stock solution and [ 111 In]InCl3 was "recovered". Radiolabeling of DOTA-peptides with the stabilized [ 111 In]InCl3 resulted again in acceptable radiochemical yields. In addition, we report convenient iTLC systems that allow distinguishing between [ 111 In]InCl3, the formed unknown 111 In-species, radiocolloids, and radiolabeled peptides (DOTANOC). Highlights: The transformation of [ 111 In]InCl3 in commercial 111 In-solutions into a new unreactive species leads to reduced RCYs. Method to quantify the unreactive 111 In species by TLCs. Method to prevent the formation of unreactive 111 In-species and improve RCY.